Changes in emotions and worries during the Covid-19 pandemic: an online-survey with children and adults with and without mental health conditions - Rothe, Josefine; Buse, Judith; Uhlmann, Anne; Bluschke, Annet; Roessner, Veit (Child and adolescent psychiatry and mental health, 2021)
The novel coronavirus disease (Covid-19) has spread quickly worldwide with dramatic consequences on our daily lives. Adverse psychosocial consequences of Covid-19 might be particularly severe for children and adolescents, parents of young children and people with mental health conditions (mhc), who are more prone to the experience of psychosocial stress and who are more dependent on the access to professional psychosocial support. The present survey therefore aimed to explore perceived stress and the emotional responses of children and adolescents as well as adults with and without mhc during the social restrictions due to the Covid-19 pandemic. The survey gathered information about 284 children and adolescent (parent-on-child-reports) and 456 adults (including 284 parents, self-reports). The participants were allocated to four groups: children and adolescents with mhc, children and adolescent without mhc, adults with mhc and adults without mhc. The survey included general questions about socio-demographic characteristics and mental health status, the CoRonavIruSHealth Impact Survey and the Perceived Stress Scale (only data on adults). Wilcoxon signed-rank tests were used for comparing the emotional responses during the Covid-19 pandemic with emotions before the Covid-19 pandemic. Independent sample t-test were used to compare the level of perceived stress between the adult groups, linear regression analyses were conducted to examine which variables predicted perceived stress during the Covid-19 restrictions. An increase to the worse during the Covid-19 restrictions was observed for most emotions and worries in all four groups (children and adolescents with mhc, children and adolescents without mhc, adults with mhc, adults without mhc). Contrary to our expectations, a greater number of emotions worsened significantly for children and adolescents as well as adults without mhc as compared to those with mhc. We found higher perceived stress in parents as compared to adults without children in the same household and in adults with mhc as compared to those without mhc. Covid-19-related social restrictions and potential health risks seem to affect emotions and perceived stress in children, adolescents and adults. Especially, Covid-19 seems to be have worsened the mental well-being of children and adolescent and their families, who were mentally healthy before the Covid-19 pandemic.